2019
DOI: 10.3390/geosciences9090369
|View full text |Cite
|
Sign up to set email alerts
|

Instant Attraction: Clay Authigenesis in Fossil Fungal Biofilms

Abstract: Clay authigenesis associated with the activity of microorganisms is an important process for biofilm preservation and may provide clues to the formation of biominerals on the ancient Earth. Fossilization of fungal biofilms attached to vesicles or cracks in igneous rock, is characterized by fungal-induced clay mineralization and can be tracked in deep rock and deep time, from late Paleoproterozoic (2.4 Ga), to the present. Here we briefly review the current data on clay mineralization by fossil fungal biofilms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 91 publications
(261 reference statements)
1
14
0
Order By: Relevance
“…As colonies age, they begin to fill the entire pore space and eventually become mineralized by clays and/or iron oxides (Ivarsson et al, 2015a;Sallstedt et al, 2019). Microbial growth and subsequent mineralization is thus a major factor in the secondary filling of voids along with abiotic precipitation of zeolites and carbonates.…”
Section: Colonization Of Igneous Rockmentioning
confidence: 99%
See 4 more Smart Citations
“…As colonies age, they begin to fill the entire pore space and eventually become mineralized by clays and/or iron oxides (Ivarsson et al, 2015a;Sallstedt et al, 2019). Microbial growth and subsequent mineralization is thus a major factor in the secondary filling of voids along with abiotic precipitation of zeolites and carbonates.…”
Section: Colonization Of Igneous Rockmentioning
confidence: 99%
“…In fact, clay authigenesis seems to play a ubiquitous part in biofilm formation and preservation, in the deep crust as well as in the shallower surface realm (e.g., Ferris et al, 1986Ferris et al, , 1987 ; Konhauser and Urrutia, 1999). In the deep igneous crust of both land (Drake et al, 2017a(Drake et al, , 2017b and oceans (e.g., Ivarsson et al 2013a, 2015cBengtson et al, 2014), fungal biofilms in particular seem to be preserved with authigenic clay minerals suggesting an important link between the biological cell and clay species such as Al, Si, Fe, and Mg. To evaluate the effect of host rock geochemistry on the precipitating clay minerals associated with fossil microbial biofilms, Sallstedt et al (2019) investigated several sites differing in ambient redox degree, and suggested that swelling smectites of montmorillonite type dominate the fossil related clay mineralogy at both oxic seamounts and deep anoxic continental granite environments. This, in turn, suggests that life's presence at depth in the crust has a greater effect than previously known on the geochemistry of secondary alteration products like clay minerals and that biology, in fact, may play a large role in the precipitation of authigenic secondary minerals in the igneous subsurface (Sallstedt et al, 2019).…”
Section: Fossil Record In Igneous Oceanic Crustmentioning
confidence: 99%
See 3 more Smart Citations